Job embeddedness and voluntary turnover in the face of job insecurity - Peltokorpi, Vesa; Allen, David G. (Journal of organizational behavior, 2024)
Summary Two important contributions to the understanding of voluntary turnover are the ideas that employees become embedded in a net or web of restraining forces on‐ and off‐the‐job and that they experience varying degrees of control and desire that yield proximal withdrawal states explaining turnover motivations. We build on these ideas in two multi‐wave studies to study job insecurity, one of the most common work stressors and top concerns among employees around the world. Study 1 demonstrates that job search mediates the positive relationship between job insecurity and voluntary turnover, and that employees higher in on‐the‐job embeddedness are less likely to search for jobs despite job insecurity. Study 2 demonstrates that turnover intention mediates the positive relationship between job insecurity and voluntary turnover, and that employees higher in on‐the‐job embeddedness are less likely to contemplate quitting despite job insecurity. However, off‐the‐job embeddedness had opposite interactive effects, exacerbating the relationship of job insecurity with turnover.